Maternal and neonatal outcomes in vacuum assisted births in the government tertiary care hospital in Mandya: a retrospective record-based study - M., Shwetha; N., Shilpa M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Vacuum extraction and forceps are the two options when an instrument is needed to facilitate a vaginal birth. Vacuum extraction has recently gained popularity because of new designs of vacuum cups with reduced risk of injury to the neonate. Vacuum extraction is one of the evidence-based interventions that can prevent complications by shortening the second stage of labour. The present study has been carried out to evaluate the maternal and neonatal morbidity, mortality and failure associated with vacuum assisted vaginal deliveries, at a Government tertiary care hospital in Mandya, Karnataka, India. Methods: The study was a record-based study including a total of 207 women who underwent vaginal assisted delivery in the form of vacuum assisted deliveries in a period of 6 months from January 2019 to June 2019 at the Government tertiary care hospital in Mandya, Karnataka, India. Records of women who had vacuum assisted deliveries and records of their newborn children were accessed. Results: In our study 41.5% of the subjects were in the age group of 21-25 years. Nearly 3/4th (74.4%) of the subjects were primigravida. More than half (54.1%) of the study subjects had to be put under vacuum assisted techniques for delivery because of the prolonged second stage of labour, failure rate was 0.4%. Out of 207 vacuum assisted deliveries maternal complication rate was 8.21%, 17.3% neonates had NICU admission and 14.97% had perinatal complications. Conclusions: Vacuum assisted vaginal delivery is comparatively a better choice in preventing the complications caused due to prolonged second stage of labour thus reducing the cesareans rate. It is a safe alternative to cesareans delivery in rightly chosen case. Vacuum assisted delivery by a skilled person and a proper technique is associated with lesser maternal and neonatal morbidity.